Agility and digitalization: why strategic agility is a success factor for mastering digitalization – evidence from Industry 4.0 implementations across a supply chain - Pfaff, Yuko (International Journal of Physical Distribution & Logistics Management, 2023)
Purpose: This paper addresses the emergence of strategic agility as adaptive capability to face the need to adapt to a constantly changing environment. Special emphasis is paid to governance mechanisms as a microfoundation of dynamic capabilities, investigating the dynamics and outcome in regards to the digitalization of supply chains and its socio-economic relations of its members. Design/methodology/approach: A multiple-case study method is applied to explain the impact of a digitalization initiative in the form of an I4.0 implementation in a supply chain context. Building on qualitative in-depth interviews of experts in managerial positions, 16 cases from the manufacturing industry involving an I4.0 implementation across the supply chain were analyzed. Based on a conceptual design science approach, the CIMO logic (context, intervention, mechanisms and outcome) framework is used to investigate the interplay between agility as a dynamic capability and governance mechanisms. Findings: The studied cases demonstrate an intensification of synergistic combinations of inter-firm resources to manage digitalization across the supply chain (SC). With the implementation of I4.0, competitive advantage along the SC takes higher priority over the competitive advantage in the individual or dyadic perspective. Strategic agility as a dynamic capability to cope with and adapt to the changing environment is hereby crucial emphasizing relational SC governance (SCG) as essential as a microfoundation to adjust the structure and management of SCs. Relationships, which allow competitive advantage as a SC balance out traditional power mechanisms within the SC hierarchy. Trust, collaboration and flexibility, aligned with common incentives in generating competitive advantages enable the SCs to mitigate uncertainty and risk while preventing opportunistic behavior. Practical implications: The study offers SCM managers in-depth insights into strategic agility and how to address the recent challenge of digitalization successfully. Identifying crucial dynamics within SCG mechanisms based on first-hand use cases, practical success factors for implementing I4.0 to optimize effectiveness and efficiency can be derived how to structure and manage future SCs. Originality/value: This paper contributes to the first insights examining the implications of digitalization and the role of strategic agility as a capability to adapt. Investigating the microfoundation of governance within this capability, this research provides insights on the socio-economic level, while discussing specific mechanisms how relationships of SCs evolve proposing relevant insights for future research.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Case study; Industry 4.0; Strategic agility; Supply chain governance; Supply chain management